2017
DOI: 10.1128/mbio.01874-17
|View full text |Cite|
|
Sign up to set email alerts
|

Bacteriophage Transcytosis Provides a Mechanism To Cross Epithelial Cell Layers

Abstract: Bacterial viruses are among the most numerous biological entities within the human body. These viruses are found within regions of the body that have conventionally been considered sterile, including the blood, lymph, and organs. However, the primary mechanism that bacterial viruses use to bypass epithelial cell layers and access the body remains unknown. Here, we used in vitro studies to demonstrate the rapid and directional transcytosis of diverse bacteriophages across confluent cell layers originating from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
307
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(320 citation statements)
references
References 61 publications
10
307
0
3
Order By: Relevance
“…However, it is unclear how the M13 phage particle (7 × 900 nm) meets size restrictions for particles that can be uptaken by clathrin‐dependent endocytosis (less than 200 nm in diameter) . Epithelial transcytosis of phages was recently observed in vitro by Barr et al Transcytosis has been proposed as the major way of phage absorption in the gastrointestinal tract . The general ability of microorganisms to translocate from the gut to systemic circulation has been well documented, and it is determined not only by microbial size, but also by other factors for example presented molecular patterns.…”
Section: Entering the Systemmentioning
confidence: 99%
“…However, it is unclear how the M13 phage particle (7 × 900 nm) meets size restrictions for particles that can be uptaken by clathrin‐dependent endocytosis (less than 200 nm in diameter) . Epithelial transcytosis of phages was recently observed in vitro by Barr et al Transcytosis has been proposed as the major way of phage absorption in the gastrointestinal tract . The general ability of microorganisms to translocate from the gut to systemic circulation has been well documented, and it is determined not only by microbial size, but also by other factors for example presented molecular patterns.…”
Section: Entering the Systemmentioning
confidence: 99%
“…Bacteria, phages and eukaryotes have co‐evolved together in a close symbiotic relationship. Although phages are viruses that infect bacteria, it has been shown that they can penetrate epithelial cell layers and spread throughout the body . It is therefore not surprising that the eukaryote host directly interacts with the phages cohabiting with its commensal bacteria .…”
Section: The Future Of Phage Therapy In Gastrointestinal Diseasesmentioning
confidence: 99%
“…It has been demonstrated that phages cannot attach to bacteria, which do not have a specific receptor. However, these bacterial cells can become sensitive through membrane vesicle mechanisms . Phage‐resistant Bacillus subtilis becomes sensitive to the lytic phage SPP1 when co‐cultured with the sensitive strain.…”
Section: Phage Therapymentioning
confidence: 99%
“…A non‐specific recognition of phages also leads to other mechanisms of endocytosis by utilising vesicles in the cells. Phages are transferred to lysosomes and then inactivated …”
Section: Phage Therapymentioning
confidence: 99%
See 1 more Smart Citation